2017
DOI: 10.1136/medhum-2017-011198
|View full text |Cite
|
Sign up to set email alerts
|

Love as delusion, delusions of love: erotomania, narcissism and shame

Abstract: Erotomania has a long, colourful history in psychiatry. It is a rare condition in which the patient ('subject') develops the belief that he or she is loved from afar by another person ('object'). The subject is generally female, though men predominate in forensic samples. The object is generally perceived to belong to a higher social class, reflecting a sociopolitical element in the construction of love. Erotomania requires active treatment and risk management as it can be associated with stalking and other of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“… 5 Styron, 1990 ; Manning, 1994 ; Wurtzel, 1995 ; Foster Wallace, 1998 ; Wolpert, 1999 ; Solomon, 2001 ; Stirman and Pennebaker, 2001 ; Belle Doucet, 2003 ; O’Brien, 2004 ; Broome, 2005 ; Fuchs, 2005 ; Barton et al, 2008 ; Westerbeck and Mutsaers, 2008 ; Radden, 2009 ; Stein, 2012 ; Flint and Kendler, 2014 ; Opel et al, 2014 ; Ratcliffe, 2014 ; Trigg, 2016 ; Kelly, 2017a , b ; Kirk et al, 2017 ; Stanghellini, 2017 . …”
unclassified
“… 5 Styron, 1990 ; Manning, 1994 ; Wurtzel, 1995 ; Foster Wallace, 1998 ; Wolpert, 1999 ; Solomon, 2001 ; Stirman and Pennebaker, 2001 ; Belle Doucet, 2003 ; O’Brien, 2004 ; Broome, 2005 ; Fuchs, 2005 ; Barton et al, 2008 ; Westerbeck and Mutsaers, 2008 ; Radden, 2009 ; Stein, 2012 ; Flint and Kendler, 2014 ; Opel et al, 2014 ; Ratcliffe, 2014 ; Trigg, 2016 ; Kelly, 2017a , b ; Kirk et al, 2017 ; Stanghellini, 2017 . …”
unclassified
“…Stößt die Verliebtheit nicht auf Erwiderung, verblasst sie mit der Zeit, führt möglicherweise zu anderen temporären psychiatrischen Störungsbildern wie einer akuten Belastungsreaktion oder einer Anpassungsstörung. "Die Liebe geht, der Wahn bleibt", wie Kelly es formulierte [21].…”
Section: Liebeswahn Heuteunclassified
“…The most frequent correlation between female stalkers and erotomania delirium is known; several studies estimate to be more frequent in females, a condition that would increase the risk of violence, representing a specific risk factor of violent behaviour (Kelly, 2017). Kraepelin suggested that erotomania illusions may serve as compensation for delusions of life (Kelly, 2017 from Kraepelin andRobertson 1921) and that they may have a relationship with unfulfilled narcissistic, heterosexual or homosexual impulses (Kelly, 2017).…”
Section: Stalking and Psychopathologymentioning
confidence: 99%
“…The most frequent correlation between female stalkers and erotomania delirium is known; several studies estimate to be more frequent in females, a condition that would increase the risk of violence, representing a specific risk factor of violent behaviour (Kelly, 2017). Kraepelin suggested that erotomania illusions may serve as compensation for delusions of life (Kelly, 2017 from Kraepelin andRobertson 1921) and that they may have a relationship with unfulfilled narcissistic, heterosexual or homosexual impulses (Kelly, 2017). Traditionally, erotomania is classified as primary or secondary (Kelly, 2005): secondary erotomania may coexist with other psychiatric disorders, such as schizophrenia, bipolar affective disorder, Fregoli syndrome, Capgras syndrome, folie à deux and a multitude of other conditions (Kelly, 2017from Kennedy et al 2000.…”
Section: Stalking and Psychopathologymentioning
confidence: 99%